Analisis Keputusan Penumpang Dalam Menggunakan Kapal KM. Egon - Moto, Ardianus Ardanah; Wibowo, Purnomo Ari; Sumarsono, Wasi; Santoso, Wahyudi; Supriyanto, Supriyanto; Samekto, Agus Aji; Kusdibyo, Kusdibyo (Fakultas Teknik Universitas Maritim AMNI Semarang, 2023)
Ship KM. Egon is one of PT Indoneisan National Shiiping fleets that seves the Indonesian people for smooth sea transportation. This ship is a ship made in Germany in 1991 with a length of 94,30 meters and a windth of 16 meters which is one of the means of transportation that crosses various islands. In one voyage this ship is capable of transportation 500 pax of vehicles, loads of goods passengers with a capacity of 500 passengers with the destination of KM ship. Egon it self is Sheet Harbor, Waingapu Port, Surabaya Port, Batulicin Port, and Pare-pare Port. This study aims to determine the effect of Quality/Service Quality, Corporate Image, Safety Assurance on Passenger’s Decisions to Use the KM Ship Egon especially at PT. Pelni Surabaya Branch, the population in this study were passengers on the KM Egon ship owned by PT. Pelni Surabaya Branch and the sampels used in this study were 92 respondents. Data collection methods used are observation (Observation), interviews, and distribution of questionnaires. The sampling technique used is non-probability sampling purposive sampling type, then the data is analyzed using multiple linear regression with the help of (software) Statistical Package For Social Science (SPSS) Version 26. The regression formulation in this study is as follows: Y = 1.785 + 0,310X1 + 0,202X2 + 0,220X3 + µ. From this equation, it is known that the most dominant variable influencing passenger decisions is the corporate image variable with a regression coefficient of 0.202. The R2 (R Square) test obtained results of 0.517 or 51,7% which means that Passenger Decisions are influenced by the variables of Quality/Service Quality, Corporate Image, Safety Assurance which are 51,7% and other factors that affect Shipping Safety at PT. Pelni Surabaya Branch, which is 48,3%.